2005
DOI: 10.1017/s0001924000000592
|View full text |Cite
|
Sign up to set email alerts
|

2D numerical study of circular synthetic jets in quiescent flows

Abstract: 2D numerical simulations of flows generated by a synthetic jet actuator with a circular orifice were conducted at two different diaphragm displacement settings, one representing a typical laminar case and the other a fully turbulent case. The flow in the cavity was included in the computation in order to provide more accurate predictions. A velocity boundary condition was applied at the neutral position of the diaphragm to account for its temporal deformation. Comparisons were made between the computational re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 9 publications
4
48
1
1
Order By: Relevance
“…The timestep used for the simulations is T/80. A sensitivity study undertaken previously showed that the choices of mesh size and time-step used in the present study are adequate [9].…”
Section: Methods For Validationmentioning
confidence: 81%
See 4 more Smart Citations
“…The timestep used for the simulations is T/80. A sensitivity study undertaken previously showed that the choices of mesh size and time-step used in the present study are adequate [9].…”
Section: Methods For Validationmentioning
confidence: 81%
“…The capability of Fluent in simulating both laminar and turbulent flows of circular synthetic jets in quiescent conditions has been validated using PIV results [9]. According to the experimental observation, the initial vortex rings and near-field flows of all the selected cases to be presented here are laminar.…”
Section: Methods For Validationmentioning
confidence: 99%
See 3 more Smart Citations